Molecular epidemiology and pathogenomics of extended-spectrum beta-lactamase producing- Escherichia coli and - Klebsiella pneumoniae isolates from bulk tank milk in Tennessee, USA - Gelalcha, Benti D.; Mohammed, Ruwaa I.; Gelgie, Aga E.; Kerro Dego, Oudessa (Frontiers in Microbiology, 2023)
Introduction The rise in extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae in dairy cattle farms poses a risk to human health as they can spread to humans through the food chain, including raw milk. This study was designed to determine the status, antimicrobial resistance, and pathogenic potential of ESBL-producing -E. coli and -Klebsiella spp. isolates from bulk tank milk (BTM). Methods Thirty-three BTM samples were collected from 17 dairy farms and screened for ESBL-E. coli and -Klebsiella spp. on CHROMagar ESBL plates. All isolates were confirmed by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) and subjected to antimicrobial susceptibility testing and whole genome sequencing (WGS). Results Ten presumptive ESBL-producing bacteria, eight E. coli, and two K. pneumoniae were isolated. The prevalence of ESBL-E. coli and -K. pneumoniae in BTM was 21.2% and 6.1%, respectively. ESBL-E. coli were detected in 41.2% of the study farms. Seven of the ESBL-E. coli isolates were multidrug resistant (MDR). The two ESBL-producing K. pneumoniae isolates were resistant to ceftriaxone. Seven ESBL-E. coli strains carry the blaCTX-M gene, and five of them co-harbored blaTEM-1. ESBL-E. coli co-harbored blaCTX-M with other resistance genes, including qnrB19, tet(A), aadA1, aph(3’’)-Ib, aph(6)-Id), floR, sul2, and chromosomal mutations (gyrA, gyrB, parC, parE, and pmrB). Most E. coli resistance genes were associated with mobile genetic elements, mainly plasmids. Six sequence types (STs) of E. coli were detected. All ESBL-E. coli were predicted to be pathogenic to humans. Four STs (three ST10 and ST69) were high-risk clones of E. coli. Up to 40 virulence markers were detected in all E. coli isolates. One of the K. pneumoniae was ST867; the other was novel strain. K. pneumoniae isolates carried three types of beta-lactamase genes (blaCTX-M, blaTEM-1 and blaSHV). The novel K. pneumoniae ST also carried a novel IncFII(K) plasmid ST. Conclusion Detection of high-risk clones of MDR ESBL-E. coli and ESBL-K. pneumoniae in BTM indicates that raw milk could be a reservoir of potentially zoonotic ESBL-E. coli and -K. pneumoniae.